2020
DOI: 10.1055/s-0040-1716413
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Trochlear Morphology from Native Using a Femoral Component Interfaced with an Anatomical Patellar Prosthesis in Kinematic Alignment and Mechanical Alignment

Abstract: Patellofemoral complications following total knee arthroplasty can be traced in part to alignment of the femoral component. Kinematic alignment (KA) and mechanical alignment (MA) use the same femoral component but align the component differently. Our objective was to determine differences in trochlear morphology from native for a femoral component interfaced with an anatomical patellar prosthesis in KA and MA. Ten three-dimensional femur-cartilage models were created by combining computed tomography and laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…The 2D radiographic findings of the present study, which showed a femoral component with a PTA of 6° valgus did not include the Q-angle in MA TKA simulations, is consistent with 3-D analysis studies that showed that MA TKA does not restore native trochlear morphology [14,22,24]. For example, a study of 45 femoral component designs aligned mechanically in 4116 3-D CT femoral models showed that 41% of the PTA fell out of the range of the native trochlear angle, representing a potential source for biomechanical imbalance, which manufacturers may need to take into account for future implant designs [24].…”
Section: Discussionsupporting
confidence: 89%
“…The 2D radiographic findings of the present study, which showed a femoral component with a PTA of 6° valgus did not include the Q-angle in MA TKA simulations, is consistent with 3-D analysis studies that showed that MA TKA does not restore native trochlear morphology [14,22,24]. For example, a study of 45 femoral component designs aligned mechanically in 4116 3-D CT femoral models showed that 41% of the PTA fell out of the range of the native trochlear angle, representing a potential source for biomechanical imbalance, which manufacturers may need to take into account for future implant designs [24].…”
Section: Discussionsupporting
confidence: 89%
“…One reason for the low incidence of reoperation for patellofemoral symptoms is that KA with a MA d -FC restores patellofemoral kinematics and contact pressure distribution closer to the native knee than MA with a MA d -FC [ 24 , 25 ]. Another is that the 3-dimensional native trochlear morphology is more closely restored with KA than MA when assessed with a variety of MA d -FC [ 1 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Riviere et al reported a high degree of discrepancy between native and prosthetic trochlear alignment in kinematically aligned TKR, with a more valgus orientation of the latter [25]. In additional studies, this discrepancy was also shown for mechanical alignment [13, 26]; this could be interpreted as an inherent limitation of implant designs. Barink has already proposed a more truly anatomical femoral configuration, with a more medially oriented trochlea [2].…”
Section: Discussionmentioning
confidence: 99%